Parametric study on excitation temperature and electron temperature in low pressure plasmas - Park, Hoyong; Choe, Wonho (Current applied physics, 2010)
This work aims at investigation of the validity of the electron excitation temperature ( T exc) by optical emission spectroscopy (OES) as an alternative diagnostic to the electron temperature ( T e). The excitation and the electron temperatures were measured at a wide range of gas pressures and input powers in different plasmas such as capacitively-coupled, inductively-coupled, and magnetron direct current plasmas. As a result, both temperatures were found to decrease with an increase in pressure, whereas they not very dependent on power, indicating that T exc showed a tendency identical to that of T e as pressure and power were varied. This result suggests that T exc measurement can be an alternative diagnostic for T e measurement once the ratio of the two temperatures is found in advance through a calibration experiment especially for low pressure high electron density industrial processing plasmas in which probe measurements are limited.